2019
DOI: 10.1021/acsami.8b22386
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Glyphosate Adsorption Behavior and Mechanism by a MnFe2O4@Cellulose-Activated Carbon Magnetic Hybrid

Abstract: To enhance the removal of the negatively charged organophosphorus pesticide (OPP) glyphosate (GLY), we prepared a positively charged MnFe2O4@cellulose activated carbon (CAC) hybrid by immobilizing MnFe2O4 nanoparticles on the CAC surface via a simple one-pot solvothermal method, scanning electron microscopy, BET, transmission electron microscopy, IR, Raman, X-ray diffraction, and X-ray photoelectron spectroscopy analysis which proved the successful synthesis of MnFe2O4 with a particle size of 100–300 nm. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(19 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…The pore structure of g-C 3 N 4 @HTLcs/HA100 is not easy to be blocked by the adsorbate because it contains a cross-linked pore structure and a typical layered structure. Moreover, compared to the adsorbents from previous studies, the as-obtained g-C 3 N 4 @HTLcs/HA100 showed a great performance of TL, DP, and GH adsorption (Table ). The g-C 3 N 4 @HTLcs/HA100 composites could be easily regenerated by desorption of the organics.…”
Section: Resultsmentioning
confidence: 81%
“…The pore structure of g-C 3 N 4 @HTLcs/HA100 is not easy to be blocked by the adsorbate because it contains a cross-linked pore structure and a typical layered structure. Moreover, compared to the adsorbents from previous studies, the as-obtained g-C 3 N 4 @HTLcs/HA100 showed a great performance of TL, DP, and GH adsorption (Table ). The g-C 3 N 4 @HTLcs/HA100 composites could be easily regenerated by desorption of the organics.…”
Section: Resultsmentioning
confidence: 81%
“…[74,75] The formation of FeÀ O and MnÀ O bonds is further confirmed by the bands at 741 and 489 cm À 1 . [76] The removal of organics on the particle surface can be achieved by a subsequent thermal treatment at 400 °C or higher, but calcination at 600 and 800 °C results in the decomposition of the spinel-type structure.…”
Section: Resultsmentioning
confidence: 99%
“…The XPS spectra of O1s in Figure c contains three peaks (533.4, 531.7 and 530.3 eV) belonging to C−O, ‐OH and Fe−O, respectively . The relative contents of the above three peaks are 21.55%, 32.56% and 45.89% before adsorption.…”
Section: Resultsmentioning
confidence: 99%